Study of Anthocyanin Pigment in Three Different Sepal Colour of Hortensia (Hydrangea macrophylla) - Hariri, Muhammad Rifqi; Nugrahaningsih, Nugrahaningsih; Balqis, Balqis (Proceeding International Conference on Global Resource Conservation, 2013)
Anthocyanin is a natural pigment that express orange, red, blue, and purple color. It can be accumulated in leaves, thorn, tuber, fruit, flower, and seed. Hortensia (Hydrangea macrophylla) which is well-known as âPanca Warnaâ, is a kind of plant that easy to thrive in different climates, can express different sepal colour as the effect of environmental factor such as soil pH. The aim of this study is to determine the level of anthocyanin pigment in three different sepal colour of Hortensia. This research is a descriptive quantitative which used randomized block design with nine replications. The object of this research is three different sepal colour of Hydrangea which obtained from Flower Gardens in Sidomulyo florist. Data obtained through the differential pH spectroscopy method and was analyzed using one way ANOVA. The result reveals that there is no significant differences of anthocyanin level among the samples.Keywords: anthocyanin pigment, sepal colour, Hortensia (Hydrangea macrophylla)